Peningkatan Jaringan Komunikasi Tertutup Berbasis Seluler Dengan Agregasi Multi Link : Studi Kasus PT. Solusi Media Semesta - Iman, Fadlul; Saputra, Elin Panca; Kusumo, Aryo Tunjung; Sismadi, Sismadi (Computer Science (CO-SCIENCE), 2024)
The increasing need for cellular-based closed communication networks in corporate environments has increasingly become a major focus for many organizations, including PT. Universal Media Solutions Jakarta. In the face of increasingly complex communication challenges and increasing data demands, the company is working to improve the efficiency and performance of its communications network. This study aims to investigate the potential of using multi-link aggregation as a solution to improve cellular communication networks at PT. Universal Media Solutions Jakarta. The multi-link aggregation method allows combining multiple communication lines to achieve increased network speed, availability, and consistency. The study will involve analyzing and testing various scenarios using multi-link aggregation technology in the company's cellular-based closed network environment. Network performance measurement will be carried out to radiate the effectiveness of the implemented solutions. In addition, technical and financial factors will also be considered to ensure the feasibility and efficiency of the proposed solution. The results of this study are expected to provide valuable insights for PT. Solusi Media Semesta Jakarta and other organizations in optimizing their closed communication network using multi-link aggregation technology. Thus, companies can increase productivity, reduce downtime, and improve service quality for their customers and internal users.